2002
DOI: 10.1038/ni880
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between dendritic cells and NK cells during viral infection

Abstract: Ly49H(+)NK1.1(+) natural killer (NK) cells are essential for the control of murine cytomegalovirus (MCMV) during the acute stage of infection. This cell subset expands at the later stages of infection in an MCMV-specific fashion. Here we demonstrate a critical interaction between Ly49H(+) NK cells and CD8alpha(+) dendritic cells (DCs) whereby the presence of Ly49H(+) NK cells results in maintenance of CD8alpha(+) DCs in the spleen during acute MCMV infection. Reciprocally, CD8alpha(+) DCs are essential for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
282
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 331 publications
(299 citation statements)
references
References 43 publications
13
282
3
1
Order By: Relevance
“…Our results with IL-18 Ϫ/Ϫ and IL-18R Ϫ/Ϫ mice conflict with a previous report implicating IL-18 in the specific expansion of Ly49H ϩ NK cells during MCMV infection (30). Due to this discrepancy, we examined NK cell proliferation in IL-18 Ϫ/Ϫ and IL-18R Ϫ/Ϫ mice in greater detail and found no significant differences in overall NK cell proliferation over the course of MCMV infection in either IL-18 Ϫ/Ϫ (Fig.…”
Section: Ly49h Signaling Through Dap12 Does Not Alter Nk Cell Responscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results with IL-18 Ϫ/Ϫ and IL-18R Ϫ/Ϫ mice conflict with a previous report implicating IL-18 in the specific expansion of Ly49H ϩ NK cells during MCMV infection (30). Due to this discrepancy, we examined NK cell proliferation in IL-18 Ϫ/Ϫ and IL-18R Ϫ/Ϫ mice in greater detail and found no significant differences in overall NK cell proliferation over the course of MCMV infection in either IL-18 Ϫ/Ϫ (Fig.…”
Section: Ly49h Signaling Through Dap12 Does Not Alter Nk Cell Responscontrasting
confidence: 99%
“…For example, a recent report suggested that the specific expansion of splenic Ly49H ϩ NK cells during MCMV infection was IL-18 dependent (30). Previous work in our laboratory indicated that the selective proliferation of Ly49H ϩ NK cells during MCMV infection was dependent on Ly49H recognition of infected cells (15).…”
Section: Dap12 Signaling Directly Augments Proproliferative Cytokine mentioning
confidence: 86%
“…These studies identified the fact that NK cells responding to MCMV acquired KLRG1, and these cells contained less intracellular IFN-␥ compared with the KLRG1 Ϫ population (12,25). This finding was extended by our recent report on NK subsets where Mac-1 ϩ CD27 Ϫ KLRG1 ϩ cells were found to produce poor levels of IFN-␥ following stimulation with IL-12 and IL-18, cytokines required for the NK cell expansion during MCMV infection (28) or when cocultured with dendritic cells (23). In addition, KLRG1 ϩ NK cells appear to preferentially down-regulate bcl-2 during the course of MCMV infection (25).…”
Section: Discussionmentioning
confidence: 67%
“…The phenotypic maturation of NK cells during MCMV-mediated NK cell division could be a result of exposure of enhanced levels of IL-18 and IL-12 because these cytokines activate NK cells, induce KLRG1 expression, and are known to be important for NK cell response to MCMV (28). Our study monitoring NK cell expansion during development and following transfer to lymphopenic hosts, without an overt inflammatory stimulus to induce these cytokines, provides strong evidence for NK cell maturation being induced by cell division.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the ligand on MCA-transformed cells undergoes immune editing by NKp46/NCR1 pressure (14), whereas the ligand on D122 cells described in this study apparently does not. Finally, we have recently shown that a ligand for NKp46/NCR1 is expressed by human and mouse b cells (27,28), and it was also demonstrated that upon human CMV infection of dendritic cells, an unknown ligand of NKp46/NCR1 is downregulated to prevent NK cell-mediated lysis of the infected dendritic cells (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 97%